Highly Connected Silicon–Copper Alloy Mixture Nanotubes as High‐Rate and Durable Anode Materials for Lithium‐Ion Batteries. (15th December 2015) - Song, Hucheng; Wang, Hong Xiang; Lin, Zixia; Jiang, Xiaofan; Yu, Linwei; Xu, Jun; Yu, Zhongwei; Zhang, Xiaowei; Liu, Yijie; He, Ping; Pan, Lijia; Shi, Yi; et al.
Abstract : Seeking high‐capacity, high‐rate, and durable anode materials for lithium‐ion batteries (LIBs) has been a crucial aspect to promote the use of electric vehicles and other portable electronics. Here, a novel alloy‐forming approach to convert amorphous Si (a‐Si)‐coated copper oxide (CuO) core–shell nanowires (NWs) into hollow and highly interconnected Si–Cu alloy (mixture) nanotubes is reported. Upon a simple H2 annealing, the CuO cores are reduced and diffused out to alloy with the a‐Si shell, producing highly interconnected hollow Si–Cu alloy nanotubes, which can serve as high‐capacity and self‐conductive anode structures with robust mechanical support. A high specific capacity of 1010 mAh g −1 (or 780 mAh g −1 ) has been achieved after 1000 cycles at 3.4 A g −1 (or 20 A g −1 ), with a capacity retention rate of ≈84% (≈88%), without the use of any binder or conductive agent. Remarkably, they can survive an extremely fast charging rate at 70 A g −1 for 35 runs (corresponding to one full cycle in 30 s) and recover 88% capacity. This novel alloy‐nanotube structure could represent an ideal candidate to fulfill the true potential of Si‐loaded LIB applications. Abstract : A novel highly interconnected Si–Cu alloy (mixture) nanotube anode structure is fabricated from amorphous Si‐coated copper‐oxide core–shell nanowires in a simple H2 reduction process. The anode materials show a high specific capacity of 780 mAh g −1 after 1000 cycles at 20 A g −1, without the use of any binder or conductive agent.